Pelatihan Media Pembelajaran Berbasis Teknologi Informasi di TK dan Playgroup Madina Luhur - Dewi Rosaria Indah; Apsari Fajar Prihantini; Riska Nur Oktaviani; Nur Aini Saura Putri; Evi Widayanti; Alfina Citra Sukmawati; Wisnu Kristanto; Suhartini Nurul Azminah (CV. Multi Kreasi Media, 2022)
Educators are the key determinant of changing learning styles in the midst of a pandemic. They are required to be more creative and innovative in conducting learning. The purpose of this community service is to increase the use of IT-based learning media for Madina Luhur Kindergarten teachers. The implementation method used in this activity is the lecture method from the speakers and practicum by the teachers with the devices they have such as mobile phones and laptops for each participant as well as mentoring by the lecturers in practicing the steps for using these web tools. For teachers, the result is an increase in their understanding and skills in using web tools such as Answer Garden and Tricider for learning materials. For lecturers, the results of this community service activity are an increase in motivation to be more active and sensitive to engage in development in the community directly, especially those related to the world of education. For Higher Education, the resulting achievement is the increasing quality of sustainable academic programs, and as a manifestation of the accountability of the Higher Education in the community. With this service, it is hoped that it can improve the skills of Madina Luhur Teachers in IT-based learning, and can apply them in the teaching and learning process at Madina Luhur Kindergarten. Keywords: Increase; Instructional Media; IT based; Madina Luhur Kindergarten